Validitas Dan Reliabilitas Depression Anxiety Stress Scale For Youth (DASS-Y) Versi Bahasa Indonesia - Muskar , Yuni Anggrayini; Rosyad, Yafi Sabila (Infomasi dan Promosi Kesehatan, 2024)
Validity testing is the process of evaluating whether a research instrument that will be used to assess a study variable may be deemed valid or not. Finding out the outcomes of validity and reliability testing on teenagers using the Indonesian DASS-Y was the aim of this study. With 105 teenage respondents, a quantitative approach was employed in this study. The findings indicated that, with a value of 1.00, the questionnaire's validation value was deemed practical, very relevant, and had high validity. The findings of the DASS-Y instrument in the Indonesian version were deemed to be both valid and reliable, with the reliability score test being.930 and the validity test Correlatet item-total correlation score rage.328-.753.